History of the Formation of Ancient Medicine in Central Asia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Central Asia is one of the ancient civilizations, it is here that the first cities, scientific centers, academies and madrasas were formed, the first views on the study of nature and medicine were formed, and on this basis, medicine, astronomy, meteorology, geodesy and exact sciences were highly developed. The Avesta, Behustun rock inscriptions, Indian, Chinese, Greco-Roman sources, as well as the medical works of ancient and medieval Eastern scholars and their significance are described in this article.